Extraction of Gelatin from Salmon Skin - Nurin Faihana,; Hasan Zuhudi Bin Abdullah, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The primary source to produce gelatin is porcine and bovine. However, the usage of mammalian gelatin leads to a few diseases, such as bovine sponge encephalopathy, transmissible spongiform encephalopathy, and hand-foot-mouth disease. Besides, some religions restricted their believers to consume porcine and bovine gelatin, for instance, Muslim, Hindu, and Jewish. In this aspect, the polemic has cause anxiety to the public. Hence the demand for gelatin from non-mammals has been an uprising. Next, the production of gelatin from fish by-products is considered as a wise solution to this problem. Furthermore, the vast waste generated by fish after filleting, such as skin, scales, and bones, causes a great expense for disposal. Other than that, recycling aquatic by-products is one of the ways to save the environment. Therefore, the objectives of gelatin extraction from salmon skin are to extract type-A gelatin from salmon skin and determine the melting temperature. Then, the dry gelatin obtained will be weighed to calculate the yield percentage and compared it with mammalian gelatin. Consequently, the functional groups will be studied using FTIR analysis that indicates the gelatin content. The salmon skin gelatin will be extracted with controllable parameters in this experiment which are different pretreatment times (8, 16, and 24 hours) and hydrochloric acid concentration (0.05, 0.10, 0.50, 1.00 M). Results from the research focused show that salmon skin gelatin has a lower yield percentage when the pretreatment time increase. The highest yield of 12.71 % was spotted at 0.50 M HCl during 8 hours. The expected result of bloom strength decrease as the pretreatment time increase and the concentration of HCl decrease. Besides, salmon skin gelatin possesses a lower melting temperature within the range of 10.7 °C to 11.5 °C. Amide I and amide II in FTIR analysis indicate the gelatin content. Thus, the type-A salmon skin gelatin successfully extracted.